Edge-halogenated graphene nanoplatelets with F, Cl, or Br as electrocatalysts for all-vanadium redox flow batteries. (August 2016) - Park, Minjoon; Jeon, In-Yup; Ryu, Jaechan; Jang, Haeseong; Back, Jong-Beom; Cho, Jaephil
Abstract: The catalytic activity of V 2+ /V 3+ and VO 2+ /VO2 + redox couples on the halogen-doped graphene nanoplatelets (F-, Cl-, and Br-GNPs) is studied by ball-milling graphite flakes with fluorine (F2 ), chlorine (Cl2 ), and bromine (Br2 ) molecules, respectively. Using the edge-selectively halogenated graphene materials with different edge exfoliation degrees, the vanadium redox reactions can be significantly facilitated by having abundant edge defects with large surface area in the order: Br-GNP>Cl-GNP>F-GNP. The influence of halogen functionalization on graphene nanoplatelets towards vanadium redox couples is further confirmed by stack-type vanadium redox flow batteries that demonstrates better cell performance than graphene nanoplatelets without dopant at the edges. Notably, the Br-GNP showed unique electrochemical performance of increased initial charge/discharge capacity and improved rate capability, respectively. It was found that halogen doping on graphene-based materials can promote vanadium redox reactions by creating effective active sites, and the electrocatalytic activity is dependent on edge exfoliation degree and well-preserved basal planes. Graphical abstract: Highlights: Edge-halogenated graphene nanoplatelets for vanadium redox reactions was studied. Halogen doping on graphene-based materials can promote vanadium redox reactions. A large degree of edge exfoliation by Br facilitates mass transport of vanadium ions. Br-GNP catalyst leads to decrease of cell overpotentials in VRFBs.